The basis for Canada's new low-risk drinking guidelines: A relative risk approach to estimating hazardous levels and patterns of alcohol use - Stockwell, Tim; Butt, P.; Beirness, D.; Gliksman, L.; Paradis, C. (2012)
Issue: Low-risk drinking guidelines have been developed independently in a number of jurisdictions resulting in different sets of advice with different definitions of ‘low risk’. This paper discusses some of the fundamental issues addressed by an expert advisory panel during the course of developing national guidelines for Canadians and summarises key sets of evidence that were influential. Approach: The underlying reasoning and connection between the evidence and the guidelines is discussed in relation to: (i) how to minimise risk of long-term illnesses; (ii) how to minimise risk of short-term harms, for example injury; and (iii) alcohol use during pregnancy. Both absolute and relative risks were considered in the development of the guidelines. Findings: Meta-analyses of all-cause mortality were used to identify upper limits for usual drinking levels where potential benefits and risks were balanced for the average person in comparison with lifetime abstainers (10 standard drinks per week for women, 15 for men). Emergency room studies and situational risk factors were considered for advice on reducing short-term: (i) when not to drink at all; (ii) how to reduce intoxication; and (iii) upper limits for occasional daily consumption by adults aged 25 to 64 years (3 standard drinks for women, 4 for men). Shortcomings in the research data were highlighted. Implications: It was estimated that total compliance with these guidelines at a national level would result in substantially reduced per capita alcohol consumption and approximately 4600 fewer deaths per year.